2019
DOI: 10.48550/arxiv.1910.03461
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Homomorphism obstructions for satellite maps

Abstract: A knot in a solid torus defines a map on the set of (smooth or topological) concordance classes of knots in S 3 . This set admits a group structure, but a conjecture of Hedden suggests that satellite maps never induce interesting homomorphisms: we give new evidence for this conjecture in both categories. First, we use Casson-Gordon signatures to give the first obstruction to a slice pattern inducing a homomorphism on the topological concordance group, constructing examples with every winding number besides ±1.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 17 publications
0
7
0
Order By: Relevance
“…A well-known example of satellite knots is a cable knot h K (P ) = C (r,s) (K ) that is obtained by choosing P to be the (r, s)-torus knot pushed into the interior of the S 1 × D 2 . This map h K has been investigated in [23,25,26].…”
Section: Background 21 Satellitesmentioning
confidence: 99%
“…A well-known example of satellite knots is a cable knot h K (P ) = C (r,s) (K ) that is obtained by choosing P to be the (r, s)-torus knot pushed into the interior of the S 1 × D 2 . This map h K has been investigated in [23,25,26].…”
Section: Background 21 Satellitesmentioning
confidence: 99%
“…P (U ) = U ) that admit genus-one doublypointed Heegaard diagram. Note such patterns cannot be dealt with using the obrstruction coming from the Casson-Gordon invariant due to Miller [11].…”
Section: Conjecture 15 ([7]mentioning
confidence: 99%
“…The assumption that a pattern P induces a homomorphism on the concordance group constrains the behavior of the τ -invariant under the action by P , i.e. τ (P (K)) = |w(P )|τ (K) for any knot K (see the proof of Corollary 1.9 in Section 6 or Proposition 5.4 of [11]). This together with Theorem 1.7 implies Corollary 1.9.…”
Section: Conjecture 15 ([7]mentioning
confidence: 99%
“…Many patterns can be obstructed from inducing a homomorphism by the unexciting requirement that P (U ) must be a slice knot. However, if P (U ) is slice then classical invariants such as the Alexander polynomial and the Tristram-Levine signature function cannot obstruct P from inducing a homomorphism on C [30,34]. The first interesting nonhomomorphism in the literature was therefore not identified until work of Gompf [15], who showed that the Whitehead pattern does not induce a homomorphism on C, despite being identically zero on the topological concordance group.…”
Section: Introductionmentioning
confidence: 99%
“…Later, Levine [23] and Hedden [18] used the τ invariant from Heegaard Floer homology to show that the Mazur pattern and (n, 1) cables (n > 1) also do not induce homomorphisms. Most recently, A. Miller [34] used Casson-Gordon signatures to give an obstruction to patterns inducing a homomorphism even on the topological concordance group.…”
Section: Introductionmentioning
confidence: 99%